2014
DOI: 10.2500/ar.2014.5.0083
|View full text |Cite
|
Sign up to set email alerts
|

Asthma Linked with Rhinosinusitis: An Extensive Review

Abstract: A sthma is a very complex disorder that involves the larger airways, but recent studies indicate that smaller airways play a key role in asthma exacerbation.1 Studies showed that individuals having more than two exacerbations per year have a higher degree of small airway dysfunction when compared with those with infrequent exacerbations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 74 publications
1
26
0
Order By: Relevance
“…Tan et al found that individuals with newly diagnosed CRS often presented with premorbid asthma when compared to healthy controls. These findings, in addition to those discussed earlier, suggest a bidirectional relationship and may allude to a subgroup of individuals with inflammatory and remodeling patterns that increase the likelihood of coexistent CRS and asthma …”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Tan et al found that individuals with newly diagnosed CRS often presented with premorbid asthma when compared to healthy controls. These findings, in addition to those discussed earlier, suggest a bidirectional relationship and may allude to a subgroup of individuals with inflammatory and remodeling patterns that increase the likelihood of coexistent CRS and asthma …”
Section: Discussionsupporting
confidence: 68%
“…These findings, in addition to those discussed earlier, suggest a bidirectional relationship and may allude to a subgroup of individuals with inflammatory and remodeling patterns that increase the likelihood of coexistent CRS and asthma. 22,35 Despite this, respondents with concurrent physiciandiagnosed asthma or use of asthma medications at baseline were excluded from this study. This established a respondent cohort where respondents did not have asthma at baseline and were evaluated at subsequent interviews to determine new asthma diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…Although CRS and asthma have been linked, 38 studies regarding the implications of this relationship are mixed. 25 We show here that increased fibroblasts are independent of asthma status in patients with CRSwNP.…”
Section: Discussionmentioning
confidence: 87%
“…24,25 There is also increasing evidence that the fibroblast is at least partially responsible for recruitment of inflammatory cells in CRS. 26 In vitro studies have shown that fibroblasts can be proinflammatory and ex vivo studies have revealed fibroblasts' production of a broad array of matrix products.…”
mentioning
confidence: 98%
“…There is also a role for non-pulmonary atopic disorders leading to respiratory allergies, as atopic dermatitis is a risk factor for the development of respiratory atopy and asthma (45). Other factors include colonization of specific microbes in the nasal passages, such as Staphylococcus aureus (46). The presence of allergen-specific IgE in asymptomatic individuals suggests that subclinical sensitization to allergen may be a common phenomenon (1, 47).…”
Section: Loss Of Inhaled Tolerancementioning
confidence: 99%